Impact behaviour of an innovative plasticized poly(vinyl chloride) for the automotive industry - C.A. Bernard (19680085) (2015)
Plasticized poly(vinyl chloride) (PPVC) is widely used in the automotive industry in the design of structural parts for crashworthiness applications. Thus, it is necessary to study and understand the influence of the mechanical response and mechanical properties of PPVC over a wide range of strain rate, from quasi-static to dynamic loadings. The process is also investigated using different sample thicknesses. In this work, the strain rate effect of a new PPVC is investigated over a wide range of strain rates at three temperatures and for three thicknesses. A modelling of the yield stress is also proposed. The numerical prediction is in good agreement with the experimental results. Other Information Published in: EPJ Web of Conferences License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1051/epjconf/20159402013